2019
DOI: 10.1021/acs.jafc.9b03059
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Duck Egg White N-Glycoproteome and Insight into the Course of Biological Evolution

Abstract: Protein glycosylation is a ubiquitous posttranslational modification that modulates protein properties, thereby influencing bioactivities within a system. Duck egg white (DEW) proteins exhibit diverse biological properties compared with their chicken egg white (CEW) counterparts, which might be related to glycosylation. N-Glycoproteome analysis of DEW was conducted, and a total of 231 N-glycosites from 68 N-glycoproteins were identified. Gene ontology analysis was used to elucidate the biofunctions of DEW N-gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Furthermore, these studies revealed the heterogeneity of N-glycosylation of egg white proteins and its influence on protein properties, such as the isoelectric point and molecular weight [ 2 ], and the existence of a proteinase/inhibitor regulation system and complement/immune systems in chicken egg yolk [ 3 ]. Subsequent studies of duck and quail egg N-glycoproteomes revealed differences in N-glycosylation between species and provided insight into evolution and environmental adaptability [ [4] , [5] , [6] ]. Furthermore, a quantitative glycoproteome analysis of unhatched fertilized eggs and hatched eggs over a 12-day period indicated that N-glycoprotein variations affected the utilization of egg proteins by the chicken embryo during incubation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these studies revealed the heterogeneity of N-glycosylation of egg white proteins and its influence on protein properties, such as the isoelectric point and molecular weight [ 2 ], and the existence of a proteinase/inhibitor regulation system and complement/immune systems in chicken egg yolk [ 3 ]. Subsequent studies of duck and quail egg N-glycoproteomes revealed differences in N-glycosylation between species and provided insight into evolution and environmental adaptability [ [4] , [5] , [6] ]. Furthermore, a quantitative glycoproteome analysis of unhatched fertilized eggs and hatched eggs over a 12-day period indicated that N-glycoprotein variations affected the utilization of egg proteins by the chicken embryo during incubation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another PTM, phosphorylation, was predicted in milk fat globule membrane in human colostrum and mature milk, with a key role in infant development ( Yang et al, 2020 ). Meng et al (2019) showed that N-glycoproteome proteins in duck egg white can have antibacterial effects. Altogether, many cellular BPs are known to be regulated by PTMs through their impact on signaling, gene expression, protein stability and interactions, and enzyme kinetics ( Friso and van Wijk, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanism underlying how dietary protein nutrition interacts with the egg quality in laying hens is still unclear. The small peptides are widely acknowledged to be implicated in the regulation of protein synthesis, secretion, and glycosylation ( 21 , 22 ), which are three important processes of albumen formation ( 21 , 23 ). It is meaningful to determine the expression of genes related to the synthesis [ OVOA, OVOB, OVALX , and OVAL , ( 24 )], secretion [ Sec13 and Sec23A , ( 25 )], and glycosylation [ POMT1 and POMT2 , ( 26 )] of protein in magnum to explore the possible mechanism of UPro regulating albumen quality.…”
Section: Introductionmentioning
confidence: 99%